Osteoporosis Self-Assessment Tool Performance in a Large Sample of Postmenopausal Women of Mendoza, Argentina. (4th March 2013) - Saraví, Fernando D.
Abstract : The Osteoporosis Self-assessment Tool (OST) is a clinical instrument designed to select patients at risk of osteoporosis, who would benefit from a bone mineral density measurement. The OST only takes into account the age and weight of the subject. It was developed for Asian women and later validated for European and North American white women. The performance of the OST in a sample of 4343 women from Greater Mendoza, a large metropolitan area of Argentina, was assessed. Dual X-ray absorptiometry (DXA) scans of lumbar spine and hip were obtained. Patients were classified as either osteoporotic (N = 1830 ) or nonosteoporotic (n = 2513 ) according to their lowest T-score at any site. Osteoporotic patients had lower OST scores (P < 0.0001 ). A receiver operating characteristic (ROC) curve showed an area under the curve of 71% (P < 0.0001 ), with a sensitivity of 83.7% and a specificity of 44% for a cut-off value of 2. Positive predictive value was 52% and negative predictive value was 79%. The odds ratio for the diagnosis of osteoporosis was 4.06 (CI95 3.51 to 4.71;P < 0.0001 ). It is concluded that the OST is useful for selecting postmenopausal women for DXA testing in the studied population.